Alcohol free? An analysis of UK and Scottish Government obesity policies' engagement with alcohol 1999-2023 - Callum Young; Benjamin Hawkins (BMC, 2024)
Abstract Background and aims Alcoholic beverages can be highly calorific yet remain largely absent from obesity policy debates. This article seeks to identify how Scottish and English obesity policies have engaged with the issue of alcohol consumption since devolution. Methods Obesity policy documents for England and Scotland from 1999 to 2023 were thematically analysed to identify their engagement with alcohol consumption. A stakeholder analysis was undertaken to identify key public health actors and commercial sector policy actors in the debate regarding the inclusion of alcohol in obesity policy. Their engagement with the issue of alcohol as an obesity policy issue was assessed through thematic analysis of consultation responses, along with documents, press releases, reports and other statements on policy (e.g. blog posts) available on stakeholder websites. Results While alcohol was recognised as a risk factor for obesity within obesity policy documents, no specific measures to address this issue were identified until a consultation on mandatory calorie labelling on alcoholic beverages was proposed in 2020. Engagement with alcohol in the policy documents was mainly limited to voluntary and self-regulatory measures favoured by industry actors who portrayed themselves as a key part of the policy solution. They used the policy focus on childhood obesity as a pretext to exclude alcoholic drink from fiscal and labelling measures. Public health NGOs, by contrast, argued that obesity measures such as mandatory calorie labelling and other obesity policies should be extended to alcoholic beverages. Conclusion There is an insufficient engagement with alcohol as an obesity policy issue within policy documents and an over-reliance on voluntary and industry-partnership approaches. Alcoholic beverages and reduced alcohol products are excluded from beverage taxes and labelling requirements in ways which are hard to justify. As with other areas of public health policy, this represents an industry-favoured policy agenda, opposed by health NGOs. Further research is needed to understand the influence of these actors on the engagement of obesity policy with alcohol.